2005
DOI: 10.1093/aob/mci010
|View full text |Cite
|
Sign up to set email alerts
|

Economy, Speed and Size Matter: Evolutionary Forces Driving Nuclear Genome Miniaturization and Expansion

Abstract: The quantitatively proportional correlation between genome size and cell size cannot be explained by purely mutational theories, as eukaryote cell volumes are causally determined by cell cycle control genes, not by DNA amounts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
297
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(312 citation statements)
references
References 134 publications
14
297
1
Order By: Relevance
“…Similar arguments have been made with respect to the evolution of ploidy level in unicellular organisms (Lewis, 1985), heterochromatic content (Cavalier-Smith, 2005) and genome size (Elser et al, 2000a;Hessen et al, 2008Hessen et al, , 2010. Of most direct relevance to our hypothesis is empirical evidence from algae and yeast suggesting that haploids are better competitors than diploids in low-P environments (Adams and Hansche, 1974;Destombe et al, 1993;Zeyl, 2004; but see Mable, 2001).…”
Section: Consequences Of High P Content For Asexual Ecologysupporting
confidence: 73%
See 1 more Smart Citation
“…Similar arguments have been made with respect to the evolution of ploidy level in unicellular organisms (Lewis, 1985), heterochromatic content (Cavalier-Smith, 2005) and genome size (Elser et al, 2000a;Hessen et al, 2008Hessen et al, , 2010. Of most direct relevance to our hypothesis is empirical evidence from algae and yeast suggesting that haploids are better competitors than diploids in low-P environments (Adams and Hansche, 1974;Destombe et al, 1993;Zeyl, 2004; but see Mable, 2001).…”
Section: Consequences Of High P Content For Asexual Ecologysupporting
confidence: 73%
“…Higher ploidy is generally associated with increased nuclear DNA content (Leitch and Bennett, 2004;Cavalier-Smith, 2005;Gregory, 2001Gregory, , 2005. This increased per-cell nuclear DNA content, however, does not necessarily translate into higher whole-organism P concentration.…”
Section: Polyploidy and Organismal Phosphorus Economicsmentioning
confidence: 99%
“…Enslavement could have started as early as shown, but the major gene transfers into host chromosomes probably postdated the nuclear envelope (Cavalier-Smith in press). (viii) Endoplasmic reticulum (ER) cisternae attached to heterochromatin via the nuclear lamina to protect DNA from shearing damage by new cytoplasmic motors (Cavalier-Smith 2005); evolution of nuclear pore complexes from the same novel eukaryotic gene family as vesicle coats (Devos et al 2004) prevented lethal complete fusion; plugging their lumen and novel nucleocytoplasmic transport proteins excluded ribosomes, allowing mitochondrial group II introns transferred to host DNA to become spliceosomal introns only afterwards (Cavalier-Smith 1991b)-not before as Martin & Koonin (2006) mistakenly suggest. (b) Logic of the bacterial cell cycle involves DNA attachment to the cell surface by proteins and membrane division between attachment sites (Cavalier-Smith 1981, 1987b.…”
Section: Mapping the Tree Onto The Fossil Record (A) The Age Of Eukarmentioning
confidence: 99%
“…Polyploids often have a somewhat lower genome size than expected from their diploid relatives (Song et al 1995;Leitch and Bennett 2004;Cavalier-Smith 2005). The mechanisms, which lead to genome downsizing in polyploids are still not understood although there are many analyses which have shown that the elimination of duplicated genes and loss of repetitive sequences could be the reasons.…”
Section: Genome Of C Albummentioning
confidence: 99%